2000
DOI: 10.1007/bf03018970
|View full text |Cite
|
Sign up to set email alerts
|

Head elevation reduces head-rotation associated increased ICP in patients with intracranial tumours

Abstract: Purpose: To quantify the effects of graded head rotation and elevation on intracranial pressure (ICP) in neurosurgical patients, before and after induction of general anesthesia.Methods: Patients with supratentorial tumours (n=12), scheduled for craniotomy with planned ICP monitoring, underwent baseline ICP measurements awake and supine (0° rotation and elevation). Incremental degrees of head rotation (15°) and of head elevation (10°) were performed independently and in combination. Paired measurements of ICP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…We found that carotid artery overlap was greater in the 80° head rotated position and this degree of head rotation with neck extension during IJV cannulation can also increase the risk of airway leakage and tracheal extubation by displacing the tracheal tube’s tip towards the vocal cords during mechanical ventilation [14, 15]. Moreover, the increase in intracranial pressure is proportional to the degree of head rotation in patients who have elevated intracranial pressure [16]. Therefore, we suggest that the 40° head rotation position is superior to the 80° head rotation position.…”
Section: Discussionmentioning
confidence: 99%
“…We found that carotid artery overlap was greater in the 80° head rotated position and this degree of head rotation with neck extension during IJV cannulation can also increase the risk of airway leakage and tracheal extubation by displacing the tracheal tube’s tip towards the vocal cords during mechanical ventilation [14, 15]. Moreover, the increase in intracranial pressure is proportional to the degree of head rotation in patients who have elevated intracranial pressure [16]. Therefore, we suggest that the 40° head rotation position is superior to the 80° head rotation position.…”
Section: Discussionmentioning
confidence: 99%
“…It is previously shown that rotation, flexion and extension movements to the head affect the CBF and increase the ICP (Hung et al. 2000, Mavrocordatos et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is previously shown that rotation, flexion and extension movements to the head affect the CBF and increase the ICP (Hung et al 2000, Mavrocordatos et al 2000. Our study showed that flexion and extension movements to the head in left and RLPs decrease the mCBF velocity, but this difference was not statistically significant (Table 3).…”
Section: Findings Related To Positions and Arterial Blood Pressure Pmentioning
confidence: 96%
“…This can be seen when there is significantly decreased compliance due to high ICP and when the patient's head is allowed to flex laterally, leading to the compression of the draining vein. [27][28][29][30][31][32] The ventilation settings are best managed with the pulmonary needs of the patient in mind. Care should be taken to avoid, if possible, ventilatory settings that can worsen increased ICP.…”
Section: Ventilatory Supportmentioning
confidence: 99%